Evaluating how treatment adherence influences cognitive remediation outcomes. (November 2022) - Seccomandi, Benedetta; Agbedjro, Deborah; Keefe, Richard S.E.; Galderisi, Silvana; Fiszdon, Joanna; Mucci, Armida; Wykes, Til; Cella, Matteo
Abstract: Background: There is evidence that Cognitive Remediation (CR) is an efficacious approach to reduce cognitive and functioning difficulties in people with schizophrenia. However, there is still a limited understanding of what influences different treatment responses. Treatment adherence has been suggested as one factor but has not been investigated systematically. Aim: To investigate how the number of CR sessions completed influences treatment outcomes. Method: This study used data from six randomised controlled trials comparing CR to a control condition. Instrumental variable analysis was used to evaluate the effect of number of treatment sessions on cognitive and functional outcomes. Logistic regression analysis was conducted to identify significant predictors of session attendance. Results: A total of 440 participants with schizophrenia spectrum diagnosis were considered. Participants were mostly men (71.6%) and had a mean age of 39.6 (SD 10.69). A higher number of CR sessions led to larger improvements in executive function and processing speed at end of therapy. However, number of sessions did not influence outcomes for working memory and functioning. Younger age and higher levels of negative symptoms at baseline were associated with higher treatment attendance. Conclusion: These findings highlight the importance of treatment adherence and underscore the importance of massed practice, at least for some cognitive outcomes. While it may be complex to assess a single session's contribution to outcome in a dose-response fashion, accessing more sessions seems associated with some cognitive benefits. Observing a relationship to functioning may require longer therapy. Highlights: The database used in this study was created by aggregating individual-level data from RCTs of Cognitive Remediation. People who attended more cognitive remediation sessions improved in executive function and processing speed after therapy. Higher treatment attendance was associated with younger age and a higher degree of negative symptoms at baseline.